Adolescents Perceptions of Gendered Influences on Mental Health: Results from a 13-Country Qualitative Study - Maddaleno-Herrera, M (ELSEVIER SCIENCE INC, 2025)
Purpose: A growing body of research supports the influence of gender norms on adolescent mental health globally. There is a lack of qualitative studies, however, that elicit adolescents own perspectives on these issues across diverse cross-cultural environments. The current study seeks to address these gaps through a qualitative exploration of gendered influences on mental health among adolescents living in 13 countries. Methods: A total of 71 focus group discussions (FGDs) with adolescents aged 12-19 years were conducted between February and June of 2021. Countries were selected to ensure geographic, economic, and cultural diversity, and included: Belgium, Chile, China, the Democratic Republic of the Congo, Egypt, Indonesia, Jamaica, Jordan, Kenya, Malawi, Sweden, Switzerland, and the United States. Within each country, FGDs were stratified by sex and age. FGDs were recorded, transcribed verbatim, and translated into English for inductive thematic analysis. Results: While adolescents reflections underscored the role of gender norms in influencing mental health, it was apparent that there are important gender differences in the nature of this relationship. According to participants, restrictive norms frequently expose girls to greater scrutiny and control, discriminatory treatment, damaging beauty standards, and gender-based violence, which have deleterious impacts on their mental health. For boys, participants highlighted emotional suppression as a central aspect of masculinity and discussed links between masculine norms and risky health behaviors. Discussion: Across a diverse group of countries, findings suggest the need for adolescent mental health prevention and promotion strategies that focus on shifting harmful gender norms during this critical developmental period. (c) 2025 Published by Elsevier Inc. on behalf of Society for Adolescent Health and Medicine.
Keywords: Adolescents; Gender norms; Masculinity; Femininity; Mental health; Qualitative study